The Geobattery Concept: A Geothermal Circular Heat Network for the Sustainable Development of Near Surface Low Enthalpy Geothermal Energy to Decarbonise Heating - Andrew Fraser-Harris; Christopher Ian McDermott; Mylène Receveur; Julien Mouli-Castillo; Fiona Todd; Alexis Cartwright-Taylor; Andrew Gunning; Mark Parsons (Earth Science, Systems and Society)
Decarbonisation of heating represents a major challenge in efforts to reach Net Zero carbon emissions, especially for countries that rely heavily on the combustion of carbon-based fossil fuels to meet heating demand such as the United Kingdom. In this paper we explore the use of near surface low enthalpy geothermal energy accessed via commercial and domestic heat pump technology. These resources may become increasingly important in decarbonisation efforts but, while they are renewable, their sustainability is contingent on appropriate management. Here, we introduce a new geothermal circular heat network concept, known as a “geobattery,” which redistributes recyclable heat from emitters to users via elevated permeability pathways in the subsurface and offers a platform to manage shallow geothermal resources. If successfully implemented the concept has the potential to provide low carbon, resilient, low-cost heating that is sustainable both in terms of heat pump performance and the shallow geothermal resource. We demonstrate the concept based on the cooling requirements of a case study data centre with existing high energy use and the potential to inject the generated heat into elevated permeability pathways in the shallow subsurface. We show that thermal recharge under these conditions has the potential to arrest subsurface temperature declines associated with closely spaced borehole heat exchangers, ensure the long-term sustainability of shallow geothermal resources for generations to come, and play an important role in the decarbonisation of heating.